Part 1: Driving renewable energy markets: the conventional approach - Cook, Jeffrey J., author; Culkin, J., author; Edmonds, C., author; Hoffer, K. H., author; Lyng, J., author; Manning, D., author; Plant, T., author; Center for the New Energy Economy, publisher (Colorado State University. Libraries, 2016)
States have long played an important role in driving energy efficiency markets. The more conventional approach to driving these markets has been the adoption of Energy Efficiency Resource Standards (EERS). This paper describes the historical adoption of EERS policies, the extent of existing market certainty associated with these policies, the outlook for future market certainty, and concludes with policy considerations for improving market certainty via EERS policy revisions.
Driving renewable energy markets: the conventional approach
Since the late 1990s, state Renewable Portfolio Standards (RPS) and Energy Efficiency Resource Standards (EERS) have been the largest drivers of the renewable energy and energy efficiency sectors. However, state target dates are quickly approaching: by 2026, 29 RPS and 11 EERS policies will need to be extended or replaced in order to maintain market certainty for continued investment and business growth. In this paper series, the Center for the New Energy Economy analyzes energy efficiency policies (Parts 1 and 2) and renewable energy policies (Parts 3 and 4). Parts 1 and 3 discuss the prospects for extending and enhancing established policies and Parts 2 and 4 propose innovative options that could work with or without an EERS and/or RPS.
Keywords: Energy policy; Renewable energy sources -- Law and legislation; energy markets